Analisis Kualitas Pelayanan Kesehatan Ibu Hamil Di Pusat Kesehatan Masyarakat Swasti Saba Kota Lubuk Linggau - Mulyati, Any; Austin, Trecy (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2021)
The study aims to measure service quality in five dimensions of service quality (Servqual), namely physical dimensions, reliability, responsiveness, assurance and empathy. This research is descriptive quantitative with a sample of 65 pregnant women who use services. The research instrument used a questionnaire. Service clinic and pharmacy, this value indicates that the quality of health services for pregnant women at Swasti Saba Puskesmas is not good. Factors that affect the quality of pregnant women's health services at the registration counter of the Swasti Saba Puskesmas are the availability of infrastructure / facilities at the Puskesmas, the availability of a comfortable waiting room, the registration process is computerized, the availability of an overview of the service flow installed at the front of the counter and human resources. In service poly, namely the availability of infrastructure / service facilities at the KIA Poly, including the availability of complete and modern examination equipment, a comfortable poly waiting room, available operational standards for services in the poly room, and a comfortable and closed maternal health service room, the competence and responsiveness of midwives in poly MCH in providing services to pregnant women. Factors that affect Pharmacy services are the availability of infrastructure / service facilities in a comfortable pharmacy waiting room, besides the availability of drugs for pregnant women that are complete with good packaging and clear rules of use and the human resources of pharmacy staff in this case related to existence, competence and power responsive pharmacy officers in providing pharmaceutical services.